Exclusive breastfeeding: awareness, perceptions and practices among antenatal multigravida women - Vaidya, Annal Abhay; Gupta, Priyanka (International Journal of Research in Medical Sciences, 2019)
Background: Breastmilk is considered the most complete source of nutrition for the new-born as it contains all necessary components such as proteins, carbohydrates and fats, water, vitamins and minerals and immunological factors required for the new-born in appropriate amounts. Breastfeeding is advantageous to the infant as well as the nursing mother in many ways. There are various benefits to the new-born both immediate as well as in the long run. Methods: A multiple-choice questionnaire was used to interview the participants during data collection. Results: Using the IBM SPSS version 20 software, descriptive analysis of the categorical variables has been presented using frequency and percentage tables. Conclusions: Though the knowledge about exclusive breast feeding was not extraordinary among the participants, they had a very favourable attitude towards the same. Almost all patients were also extremely receptive and inquisitive during the session for discussion about the same.